Building English Vocabulary Schema Retention Using Review Value Calculation for ESL Students - Cihangir Arslan; Burhan Mustafa Tanis (Research in Social Sciences and Technology- OpenED Network, 2018)
Vocabularies, the core of any language, is probably the most challenging and time-consuming part of learning a foreign language in a diverse and disperse community of learners. This study proposes an approach that can help a learner build up his/her English vocabulary volume by intensive article reading, inclusion of Google Cloud Natural Language API, Glosbe Dictionary API and the use of computing technology, the review value calculation. The review value calculation was able to determine the number of days where the new words should be reviewed and be part of the long-term memory. Result shows that students were able to increase their vocabulary acquisition skills by applying technology and computing to their study routines. Students were able to retain words fast and understand better, by employing an interactive monitoring process. If the system will be implemented carefully, it will hypothetically produce a faster technique in acquiring new vocabularies for foreign students.